Well-being, physical activity and health promotion among officers and ratings on board cargo ships: A cross-sectional study - Reck, Chiara; Dengler, Dorothee; Belz, Lukas; Harth, Volker; Oldenburg, Marcus (PloS one, 2025)
Health and well-being of seafarers working on merchant vessels is an essential area of research, given the significant physical and psychological demands placed on these workers. The present study focuses on assessing the current health status and well-being, identifying personal needs and requirements for health promotion among officers and ratings on board. A total of 583 seafarers from a German shipping company were surveyed by using a questionnaire including the standardized WHO-5-Well-being Index, PHQ-9, GPAQ and questions about the need for health measures as well as physical activity. The survey was distributed to 616 seafarers on 33 merchant ships with a response rate of 94.6%. Officers reported lower well-being compared to ratings (60.1% vs. 70.0%, p = 0.001). Regarding depressive symptoms no significant differences between the rank groups were found. Furthermore, ratings stated a significantly higher total physical activity than officers (10,437 vs. 8,035 MET-min/week, p = 0.005), while officers were significantly more sedentary compared to ratings (3.5 vs. 2.4 hours/day, p = 0.001). Seafarers also reported a high interest in sports on board (>56%) and health promotion (>60%), with a preference for digital formats and monetary incentives for participation in health programs. The impaired well-being of seafarers compared to shore-based reference groups underscores the need for targeted, digital interventions to improve the health and well-being of seafarers. The findings highlight significant differences in well-being, physical activity, and interest in health promotion between officers and ratings. Future research should apply longitudinal designs to better understand the causal relationships between occupational and socio-demographic factors with health outcomes among seafarers.